Industrial breeding and domestication of mandarin fish (Siniperca chuatsi) in Tianjin, China - Xin Luo; Wei Zhang; Yuanyuan Dai; Lin Ma; Qikang Bo; Hongzheng You; Hongqing Sun; Houfu Liu; Jufeng Jiang; Zhongzhi Chen (Fisheries and Aquatic Sciences)
This study addresses challenges in the breeding and domestication of mandarin fish (Siniperca chuatsi) in Tianjin, China, focusing on improving survival and feeding acclimation rates. A comparative analysis of single-injection and double-injection spawning methods was conducted, along with evaluating common carp (Cyprinus carpio) as initial feed. The results revealed significant differences in effect duration, with natural spawning (37.2 ± 0.8 h) being the longest, followed by the one-injection method (24.5 ± 0.5 h), and the two-injection method (18.5 ± 0.5 h). Fertilization rates also differed significantly, with the one-injection (81.33 ± 2.40%) and two-injection methods (83.03 ± 2.41%) outperforming natural spawning (73.50 ± 3.75%). The growth curves of both common carp and mandarin fish displayed nonlinear trends over time, supporting the feasibility of using common carp as an initial feed for mandarin fish. The industrial aquaculture model successfully maintained high water quality, highlighting its effectiveness in water purification. After 60 days of domestication, 91,819 juvenile mandarin fish with an average size of 7.8±0.15 cm were harvested, achieving a feed conversion ratio of 2.2 and a survival rate of 18.65%. This study demonstrates the potential for large-scale aquaculture and industrial development of mandarin fish in northern China, providing valuable insights into improving breeding and acclimation processes.